2019
DOI: 10.1155/2019/5180895
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Peritoneal Metastases: A Systematic Review of Current and Emerging Trends in Clinical and Translational Research

Abstract: Colorectal peritoneal metastases (CPM) are associated with abbreviated survival and significantly impaired quality of life. In patients with CPM, radical multimodality treatment consisting of cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemotherapy (HIPEC) has demonstrated oncological superiority over systemic chemotherapy alone. In highly selected patients undergoing CRS + HIPEC, overall survival of over 60% has been reported in some series. These are patients in whom the disease bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 104 publications
3
20
0
4
Order By: Relevance
“…It is of note that the diagnostic performance SPCCT was found to be in line with that reported for colorectal PM in humans using conventional CT, i.e. Se ranging, in function of lesion size and location, from 11 to 96% and Sp ranging from 49 to 100% 49 . However, in terms of absolute size, the Se of SPCCT in rats was much greater for lesions < 5 mm (LS-1 + LS-2) than the 11% Se for such lesions in humans (LS-1) reported by Koh et al using conventional CT 19 .…”
Section: Discussionsupporting
confidence: 85%
“…It is of note that the diagnostic performance SPCCT was found to be in line with that reported for colorectal PM in humans using conventional CT, i.e. Se ranging, in function of lesion size and location, from 11 to 96% and Sp ranging from 49 to 100% 49 . However, in terms of absolute size, the Se of SPCCT in rats was much greater for lesions < 5 mm (LS-1 + LS-2) than the 11% Se for such lesions in humans (LS-1) reported by Koh et al using conventional CT 19 .…”
Section: Discussionsupporting
confidence: 85%
“…Franko [4] analyzed the database of Analysis and Research in Cancers of the Digestive System (ARCAD) and reported that patients with isolated peritoneal metastasis had worse median survival times (16.3 months) than those with liver (19.1 months), lung (24.6 months), or lymph node (19.4 months) only respectively. Moreover the tumor biological behavior, survival outcome and therapeutic effect of isolated PM origined from CRC significantly differed from other subsets of metastatic colorectal cancer (mCRC) [6,7] . It was important to find out appropriate prognostic markers to predict survival outcome and guide surgeons to choose optimal treatment strategies for SCRPC patients.…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…For example, there is a large variability in the sensitivity of the radiological imaging ranging from CT scans, PET/CT and MRI and the variability is dependent on the anatomical site and size of the peritoneal metastases. 10 Patients registered with primary colorectal cancer n= 10,336…”
Section: The Reference Databasementioning
confidence: 99%
“…The sensitivity of a PM diagnosis is based on preoperative radiological assessment such as computer tomography (CT) scans, and has been reported with a great variance from 11% to 96%. 10 Currently, no radiological imaging is superior to an intra-operative assessment of the peritoneal cavity. 11 Registries contain large comprehensive data, and the registration of S-PM enables clinicians and researchers to monitor prevalence and incidence along with treatment methods, mortality rates and the prognosis.…”
Section: Introductionmentioning
confidence: 99%